Forming Religious Character, Discipline, And Responsibility Through The Habit of “Asnawi Tahluq” - Sukarman, Sukarman; Istiqomah, Dewi Qodar; Embong, Rahimah (Universitas Wahid Hasyim Semarang, 2024)
AbstractGlobalization has had a significant impact on education, creating competition and positive achievement, but also causing counter-social behavior. In the context of Islamic education, the formation of spiritual intelligence becomes very important. This research aims to describe the implementation of the Asnawi tahluq habit and the supporting and inhibiting factors. This research uses a qualitative method with a field research approach which is based on the philosophy of postpositivism. Data collection techniques involve observation, interviews and documentation at MTs. Matholi'ul Huda Troso. This school implements